Female mobility and gendered space in ancient Greek myth - Konstantinou, Ariadne (Bloomsbury Academic, 2018)
Goddesses on the move -- To move or not to move: the mobility of virgin goddesses -- Beginning from Hestia -- Athena's ride -- Artemis the huntress -- The mobility of Olympian wives and mothers -- Aphrodite's epic love affairs and her mobility -- The mobility of Demeter and other females in the Homeric hymn to Demeter -- Hera's mobility and her choice to remain immobile -- Heroines on the move -- Away from the paternal hearth: mobile heroines in Greek tragedy -- Mobile heroines in Greek tragedy -- Io in Prometheus bound: mobility and centrifugality -- The Danaids and Io in the geography of Suppliants -- Female mobility between myth and ritual -- Maenads at the mountain: the mobility of maenads and configurations of space in Euripides' Bacchae -- The space of the hunt in huntress myths and the Arkteia at Brauron -- From female mobility to gendered spaces: the limits of mythic imagination -- The limits of mythic imagination and of female mobility in myth -- "Glass walls" as the limits of female mobility